2016
DOI: 10.11648/j.ijnfs.20160501.13
|View full text |Cite
|
Sign up to set email alerts
|

Phenolic Content and Antioxidant Activity of Cantaloupe (<i>Cucumis melo var. cantalupensis</i>) and Food Application

Abstract: The objectives of this study were to determine phenolic content and antioxidant activity of methanolic extracts from different parts of cantaloupe (skin, seed and flesh), and to evaluate the efficiency of using cantaloupe skin wastes methanolic extracts at concentrations of 200, 400 and 600 ppm, respectively by compared with BHA on oxidative stability of mayonnaise incubated at 40°C to accelerate the oxidation for 60 days. The flesh extract give the highest yield (62.87±2.3 g extract/100 g powder) whilst the l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
7
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 34 publications
(34 reference statements)
3
7
2
Order By: Relevance
“…Similarly, these values are much higher than the values reported by Preciado-Rangel et al 26 of 4.56-6.48 GAEC100 gG 1 FW, in cantaloupe melon fruits produced using different nutrient solutions (Steiner solution, compost tea, vermicompost tea and vermicompost leachate). Also, the TPC range recorded in this study is larger than the value of 4.32 GAEC100 gG 1 FW published by El-Din Ibrahim and El-Masry 24 for the flesh of cantaloupe extracts.…”
Section: Discussioncontrasting
confidence: 79%
See 2 more Smart Citations
“…Similarly, these values are much higher than the values reported by Preciado-Rangel et al 26 of 4.56-6.48 GAEC100 gG 1 FW, in cantaloupe melon fruits produced using different nutrient solutions (Steiner solution, compost tea, vermicompost tea and vermicompost leachate). Also, the TPC range recorded in this study is larger than the value of 4.32 GAEC100 gG 1 FW published by El-Din Ibrahim and El-Masry 24 for the flesh of cantaloupe extracts.…”
Section: Discussioncontrasting
confidence: 79%
“…The highest amount of total flavonoids, corresponded to 0.09 mg catC100 gG 1 FW, was found in T 4 (VC:RS, ratio 1:4, v:v). The range of values recorded in this study, 0.06-0.09 mg catC100 gG 1 FW for the total flavonoid content, was vastly outweighed by the value of 0.20 mg REC100 gG 1 FW determined by El-Din Ibrahim and El-Masry 24 in the flesh of cantaloupe extracts. The range reported here was also lower than the range of values, 0.74-4.71 mg QECgG 1 DW, reported by Khatana et al 30 in peel extract of different cucurbits.…”
Section: Discussioncontrasting
confidence: 66%
See 1 more Smart Citation
“…Also, p-coumaric acid contents of dehydrated melon samples varied between 0.15 (infrared) and 0.88 mg/100 g (oven) while ferulic acid amounts of dehydrated melon samples change between 0.26 (infrared) and 0.91 mg/100 g (oven). Also, while quercetin amounts of dehydrated melon samples are found between 0.69 (microwave) and 1.21 mg/100 g (infrared), Masry, 2016). In other study, Vella et al (2019) reported that melon peel extract contained 2.45 mg/g gallic acid, 0.08 mg/g chlorogenic acid, 0.06 mg/g rutin, 0.09 mg/g ferulic acid, 0.57 mg/g ellagic acid, 002 mg/g quercetin and 0.32 mg/g isorhamnetin.…”
Section: Phenolic Compounds and Their Quantity Values Of Melon Dehydrated By Heating Systemsmentioning
confidence: 92%
“…Reticulate (Ghasemi et al, 2009;Tumbas et al, 2010;Isabelle et al, 2010;Ramful et al, 2011;Barros et al, 2012;Kelebek & Selli, 2014;Zhang et al, 2014;Wang et al, 2017;Stafussa et al, 2018;Zhang et al, 2018), Cu. Melo (Ismail et al, 2009;Isabelle et al, 2010;Morais et al, 2015;Ibrahim & El-Masry, 2016;Stafusa et al, 2018;Muzykiewicz et al, 2018), Cy. Oblonga (Silva et al, 2002;Magalhaes et al, 2009;Legua et al, 2013;Wojdylo et al, 2013;Szychowski et al, 2014;Kabir et al, 2015;Teleszko & Wojdylo, 2015;Umar et al, 2015;Stojanovic et al, 2017;Baroni et al, 2018;Torres et al, 2018;Sut et al, 2019), H. megalanthus (Torres-Grisales et al, 2017), M. domestica (Sun et al, 2002;Valavanidis et al, 2009;Vieira et al, 2009;Hassimotto et al, 2009;Isabelle et al, 2010;Karaman et al, 2013;Teleszko & Wojdylo, 2015;Lutz et al, 2015;Wang et al, 2015a;Raudone et al, 2017;Inal et al, 2017;Navarro et al, 2018), O. ficus-ind...…”
Section: Humanmentioning
confidence: 99%